Social Protection and Disaster Recovery - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2020)
This note highlights the critical contribution that social protection can make to a broader disaster recovery effort by helping directly to disaster-affected households. It is intended primarily for those government officials involved in organizing the post-disaster response and recovery effort who may not be familiar with social protection or the contribution it can make as part of their response and recovery plans. It also provides a high-level sensitization to the main social protection programs and their potential uses in response and recovery, including their primary strengths and limitations in post disaster settings. It is hoped that this indicative information can provide the basis and impetus for government officials leading the response and recovery effort to collaborate with their own national social protection ministries, departments and agencies in order to assess the most appropriate contribution that social protection can make in their specific country contexts, and at a much more detailed degree of technical specificity.